Effect of Dietary Zinc on Semen Quality of Cobb 500 Broiler Breeder Males - Amem, Mahmood H.M.; Al-Daraji , Hazim J. (International Journal of Poultry Science, 2011)
The purpose of the present research was to evaluate the effect of dietary supplementation with different levels of zinc (0, 50, 75, 100 mg/kg diet) on semen quality of Cobb500 broiler breeder males. The four experimental diets were as follows: T1 = the basal diet (control) without any addition (0 Zn). T2 = 50 mg Zn (pure zinc)/kg diet. T3 = 75 mg Zn (pure zinc)/kg diet T4 = 100 mg Zn (pure zinc)/kg diet. The results showed that, Zinc supplementation had significantly (p